Glass Fabric-reinforced Polyte 440-M888 Composite Laminated Subjected to Tensile Load on Warp Direction. (2015) - Száva, Ioan; Modrea, Arina; Gálfi, Botond-Pál; Munteanu, Aneta Reká
Abstract: This paper present and regarding the load-extension from preload distributions of twelve plies RT300 glass fabric-reinforced Polylite 440-M888 polyester resin specimens cut on warp direction, all these behaviors shows present nonlinear distributions. This phenomenon is due to the nonlinear behavior of the Polylite 440-M888 polyester resin since is well known that glass fibers present perfect linear distribution in tensile test. Glass fabrics manufactured from unidirectional roving represent the second most used reinforcing material after chopped strand mats. These fabrics present certain number of nodes on square centimeter, certain width and thickness, certain porosity (eye width), bending strength and feature certain surface aspect.